Abnormal uterine bleeding: a clinicohistopathological analysis - Y, Anupamasuresh; YV, Suresh; Jain, Prachi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Abnormal uterine bleeding (AUB) is one of the most common problem for the patients and the gynecologists. It adversely effects on the quality of life and psychology of women. It is of special concern in developing country as it adds to the causes of anemia. Management of Abnormal Uterine Bleeding (AUB) is not complete without tissue diagnosis especially in perimenopausal and post-menopausal women. Histological characteristics of endometrial biopsy material as assessed by light microscopy remains the diagnostic standard for the diagnosis of endometrial pathology. Methods: In our prospective study of 359 Patients of the age between 46 &73 years, clinical characteristics and the pattern of endometrial histopathology and their association in women, who present with abnormal uterine bleeding, are categorised into six groups. Results: In our study, a significant correlation of histopathology &BMI was observed with endometrial hyperplasia and malignancy in obese patient i.e. 37 out 96 and 13 out of 23 respectively. The incidence of malignancy has been increasing with the age being 1.6% in 46-50 years to 60% in 70-75 years. In our study 116 (32.3%) had hypertension, 33 patients (9.2%) had diabetes mellitus, 40 patients (11.1%) had hypothyroidism. Conclusions: We found a maximum incidence of AUB in multiparous women. Clinicohistopathological analysis of AUB revealed endometrial hyperplasia in majority of patients.